Penanganan Korban Bullying: Intervensi Konseling Kelompok dengan Pendekatan Client Centered - Sofyan Abdi; Nia Ramadatus Solihah; Afra Hasna; Nurul Khassanah; Ilma Khaerani; Muhammad Syarif Hidayat (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2024)
This research aims to explore the effectiveness of group counseling with a client-centered approach in helping students who are victims of bullying at SMK Negeri 50 Jakarta. The qualitative method with a narrative approach involved 32 class X students as a population, selected purposively from those who experienced bullying. The results of the research show that client-centered group counseling is able to provide a positive effect in handling victims of bullying in students at SMKN 50 Jakarta, students who are victims of bullying can manage their emotions in a supportive environment and feel understood and appreciated. Client-centered counseling groups emphasize the importance of empathy, unconditional acceptance, and authenticity in building an effective therapeutic relationship.